Preliminary Memorandum on Fourth Five Year Plan Andaman and Nicobar Islands - Planning Commission (Planning Commission, 1965)
An expenditure of Rs.509.705 lakhs has been incurred till the end of March, 1965 and an expenditure of Rs.300.174 lakhs is likely to be incurred during the remaining period of the Third Plan making a total of Rs.809.879 lakhs as against the Third Plan outlay of Rs.1021.900 lakhs.
Andaman and Nicobar Islands